Desafíos emocionales y psicológicos que enfrentan los cuidadores de niños con trastornos mentales del Hospital Departamental Psiquiátrico Universitario del Valle (2024)
The present research aims to identify the emotional and psychological challenges faced by caregivers of children diagnosed with emotional disorders, the state of exhaustion they may be experiencing and the possible affectations in their quality of life. The construction of the theoretical framework was elaborated from the DSM 5 diagnostic criteria (Morrison, 2015), with special emphasis on neurodevelopmental disorders, attention deficit disorder, hyperactivity, schizophrenia, depression and eating disorders and their relationship with the developmental stage of childhood; it also addresses the issue of quality of life and types of caregivers and how these positions are explained by the ecological model of Bronfenbrenner (1987). The methodology used was quantitative, making use of the Zarit scale (2011) and the Qollti-f (Cohen, et al., 2006) that evaluates the quality of life of family caregivers, which were applied to 12 people who exercise informal care of children with mental disorders, finding as a result that they usually present a degree of mild or intense exhaustion and that their quality of life is affected in areas such as self-care and privacy. Key words: emotional challenges, caregivers, emotional disorders, neurodevelopmental disorder, attention deficit hyperactivity disorder (ADHD), schizophrenia, depression, eating disorders, childhood development, quality of life, ecological model.